Market research concerning the consumption of fish and fishery products - Ancuţa Marin (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
In order to be healthy, people need essential amino acids, carbohydrates, essential fatty acids and not less than 28 vitamins and minerals. The fish is a healthy protein source with a special nutritional value, rich in essential nutrients: proteins, amino acids, vitamins A, B6, B12, D, and Omega-3. Fish, especially fish from the sea, also contain phosphorus, potassium, sodium. Nutritional needs differ from one stage of life to another, so specialists recommend dietary intake specific to different stages of life. Fats in fish are highly perishable being subjected to oxidation, therefore fresh fish is considered proper for consumption just 1 or 2 days. Fish and fish products must therefore be kept at low temperatures, being known the fact that the nutritional value of the frozen fish is almost the same as that of the fresh fish. Research methods used in this paper are "bibliography analysis" and "survey based on questionnaire". The purpose of the paper is to find out what consumer preferences are, in order to form an image of the requirements of the fish market and fish products. Given the components of fish and its importance in human nutrition, it is not without interest to form a picture of the profile of the urban consumer in Romania. The energy given to humans by eating fish and fish products is very small. The conclusion is that we do not consume fish for the caloric intake it provides but for vitamins (especially B), minerals, but especially Omega-3 it contains.
Keywords: O13; M31; Q13; 330; fish; essential nutrients; consumption; profile of fish consumer